Proposal for an innovation, entrepreneurship, and creativity festival for Federal Institutes - Pereira, Tatiana Gonçalves; Souza, Neuber Samy Ferreira de; Longhini, Tatielle Menolli (Brazilian Journal of Production Engineering, 2024)
Innovation marathons at universities lead students to develop skills and competencies that contribute to professional performance in different areas, besides providing significant personal growth to these students. This article aims to present the feasibility of the proposal for a festival of innovation, entrepreneurship, and creativity for the Federal Institute of Education, Science and Technology of Minas Gerais, Campus Governador Valadares (IFMG-GV). Using a descriptive and qualitative case study, the results show that innovation events can strengthen the entrepreneurial culture and attract investments to the region. Key contributions include the promotion of entrepreneurial skills and positive economic.
Keywords: Innovation; Entrepreneurship; Creativity